1997
DOI: 10.1161/01.cir.96.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Oral Sulfonylurea Hypoglycemic Agents Prevent Ischemic Preconditioning in Human Myocardium

Abstract: Human myocardium from patients without long-term exposure to oral hypoglycemic agents is functionally protected by preconditioning. Long-term oral hypoglycemic intake blocks the protection by preconditioning. These data suggest that ischemic preconditioning in human myocardium relies on KATP channels, and long-term inhibition of KATP channels with oral hypoglycemic agents may explain the excess cardiovascular mortality in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
141
2
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(158 citation statements)
references
References 14 publications
8
141
2
7
Order By: Relevance
“…The increase in PKG activity stimulates opening of mKATP, decreasing mitochondrial Ca 2+ overload, ROS production and prolonged opening of MPTP to maintain ATP production [29][30][31][32] . As well as its application in the myocardium, ischemic preconditioning can also be induced by brief interruptions of blood flow to other organs, particularly skeletal muscle.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The increase in PKG activity stimulates opening of mKATP, decreasing mitochondrial Ca 2+ overload, ROS production and prolonged opening of MPTP to maintain ATP production [29][30][31][32] . As well as its application in the myocardium, ischemic preconditioning can also be induced by brief interruptions of blood flow to other organs, particularly skeletal muscle.…”
Section: ■ Discussionmentioning
confidence: 99%
“…End reperfusion tissue (90 min) CK activity was determined as described (18). Tissues were homogenized in 100 vol of ice-cold isotonic extraction buffer (5,18). The assay was performed with a CK kit (Sigma) by using an automated spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…However, human myocardial tissues obtained from patients undergoing elective cardiopulmonary bypass procedures have been studied under controlled ex vivo conditions (5,6). In this experimental model, human atrial trabeculae are suspended in a blood-free physiologically oxygenated buffer bath and then exposed to an episode of simulated ischemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemia/reperfusion process triggers macrophages and activated Küpffer cells release inflammatory cytokines 6 . Glibenclamide, an anti-diabetic agent, is a K ATP channel antagonist with half-life of 4±1 hour [7][8][9] . Some experimental studies have shown a possible relationship between glibenclamide action on the K ATP channel and effects in the inflammatory process 10,11 .…”
Section: Introductionmentioning
confidence: 99%